The Role of the Notary in Increasing Tax Compliance Done by Taxpayers During Tax Planning - Aulia, Dewi Monica (Syntax Literate, 2025)
Most individuals would like to refrain from paying too much tax. Whilst governments need tax as revenue to help run its government. Tax Planning enters the realm. How to pay as minimum tax as possible without violating laws. With the emergence of a more globalized economy, and players transgressing across borders, along comes a variety of categories such as transfer pricing, the categorization of a permanent establishment, the determination of the utmost beneficial owner over a number of companies, taxable income on athletes and musicians obtained in other countries other than his/her country of residence and overall income and profits of a multinational enterprise. Implications may arise when a company is operating in one country, and reporting its profits for tax income purposes in another country. A country may feel at a loss when it is not receiving the revenue it is expecting from a company operating in its country because the company is reporting its profits in another country where the income tax rates are lower. Then comes the question, to what extent could a notary in Indonesia have in reminding and increasing compliance by taxpayers when they are at the notary’s office establishing a company with the purpose of tax planning.